Efektivitas dari Project Base Learning terhadap Siswa dalam Pembelajaran Ilmu Pengetahuan Alam - Rohmatillah, Aminatur; Ratnasari, Khurin’in (Bidayatuna, 2024)
This research aimed to discover the impact of project-based learning on students' affective learning outcomes in IPAS (Integrated thematic learning) at the elementary school level. The research employed a quantitative approach, utilizing paired t-test data analysis due to its single experimental class design. The findings of this study indicate the presence of an impact of project-based learning on students' affective learning outcomes, evident from the changes in their values or attitudes when interacting with peers or teachers after implementing the learning approach among 30 students. The advantages of implementing this practice during the learning process include: 1) Increased student enthusiasm for learning; 2) Enhanced understanding of the material; 3) Better application of understanding values and attitudes when in groups or individually. However, there are constraints and drawbacks, including: 1) Requires more time; 2) Requires adequate facility support; 3) Teachers need to be more intensive as they serve as a source of information and need to work alongside students to explore the fundamental concepts of the material to be learned; 4) Difficulty in getting students to collaborate with peers outside their groups.